2022
DOI: 10.26905/jbm.v9i1.7581
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Nilai Perusahaan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia

Abstract: This research was conducted in order to examine the effect of capital structure, profitability, and firm size on a firm's value. The research was carried out in the coal sub-sector which was listed on the Indonesia Stock Exchange (IDX) in 2016 to 2020. This type of research was quantitative research with the method of determining the sample used was purposive sampling and the research sample obtained was 16 companies. The data analysis technique used is panel data regression analysis assisted by the Eviews 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…So it can be seen that the GDP variable has a positive but insignificant effect on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. It is in line with research (Beriwisnu, 2017), (Larianti and Purbawangsa, 2019), (Pasaribu et al, 2019), (Ebenezer et al, 2019), (Ahmad et al, 2020), (Lubis et al, 2021) and (Olalere et al, 2021), who found that GDP does not affect firm value. Thus, the rise or fall of GDP in Indonesia does not affect the value of shares in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…So it can be seen that the GDP variable has a positive but insignificant effect on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. It is in line with research (Beriwisnu, 2017), (Larianti and Purbawangsa, 2019), (Pasaribu et al, 2019), (Ebenezer et al, 2019), (Ahmad et al, 2020), (Lubis et al, 2021) and (Olalere et al, 2021), who found that GDP does not affect firm value. Thus, the rise or fall of GDP in Indonesia does not affect the value of shares in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.…”
Section: Resultssupporting
confidence: 89%
“…(Bustaman and Budianto, 2016), (Isnurhadi et al, 2019) showed their result that there is a positive impact of GDP to the firm value. Other studies (Kewal, 2016), (Beriwisnu, 2017), (Pasaribu et al, 2019), (Lubis et al, 2021), (Olalere et al, 2021), founded that GDP negatively impact the firm value. So the hypothesis of GDP to the firm value could be concluded as follows:…”
Section: The Formula Of Profitabilitymentioning
confidence: 95%
“…The (Luthfiyah & Utami, 2022) found that capital structure has no effect on company value, this is because the portion of own capital (Equity) is greater than debt by maximizing company profits [15]. If the company optimizes the debt portion compared to its own capital and company profits, it will result in bankruptcy.…”
Section: The Effect Of Capital Structure On Firm Value Through Compet...mentioning
confidence: 99%
“…According to (Mitani, 2013) in his research found that capital structure can affect the company's competitive interactions in the output market which can increase profitability and firm value that is useful for investors [17]. According to Kopong, Nawir, & Permadhy, (2021) in Luthfiah & Utami (2022) argues that companies that have debt will have a high company value compared to companies that do not have debt, because with debt, investors can instill confidence in companies that will be able to operate optimally in terms of paying off their debts with the capital owned by the company so that they will believe in boldly taking greater risks and the results will be optimal and the company's tax burden can be reduced from the debt [14,15]. Hitt, et,al (2005) in (S. R. Fauziah & Sudana, 2013) states that the combination of company resources and capacity improves the competitiveness strategy and provides value for the company [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing company size impacts higher company costs, where larger companies will have increasingly increasing standards to maintain existing human resources. Kolamban et al in Luthfiyah & Utami (2022) believe that large companies' costs are high and impact increasing debt, ultimately making the company vulnerable to bankruptcy.…”
Section: Introductionmentioning
confidence: 99%